Conhecimento como recurso estratégico para obtenção de vantagem competitiva: um estudo em uma instituição de ensino superior privado - Christiano, Ana Carolina de Lucena (2014)
The higher education institutions (HEI) in Brazil, as well as other organizations, have faced constant challenges caused by changes in the organizational environment. In this environment, more specifically in the case of private institutions, the main features are related to the great competition, the highest priority on undergraduate education, the demand for improving the quality of education, low productivity, both in teaching and in research, and focus on organizational efficiency. In this context, this thesis examines, through resource-based view (RBV), the organizational knowledge is a strategic resource and source of competitive advantage in a private institution of higher education in the city of João Pessoa/PB. To this end, an extensive literature review was done addressing various issues related to the theme, including the SECI model of knowledge conversion, founded by Nonaka and Takeuchi (2008), and the model theory of resource-based view of Barney and Hesterly (2011). The research was considered to be applied, qualitative, descriptive and classified as to the procedures as, literature, case study and survey data. The study used questionnaires used to collect the data, semi-structured interview scripts and script characterization of the institution. The research took place in UNAVIDA Universidade Aberta Vida, based in the city of João Pessoa/PB, and was applied to 05 managers and 40 teachers available in the classroom. As a result of the identification of resources according to the VRIO model, it was found that one of the managers do not see knowledge as an existing resource in the education institution, unlike the others. Thus, among the remaining four, three consider knowledge as a valuable resource for the institution, but it is not rare or costly to imitate and before the competition, while a classifies knowledge as valuable, rare and costly to imitate resource, as well as it is operated by the institution. As to assertions that treat the SECI model, managers responded, mostly to "partially agree" or "strongly agree" with the statements about the socialization, externalization, combination and internalization of knowledge in the educational institution. Furthermore, the issues dealing VRIO and SECI model simultaneously, it is observed that most of the managers and teachers assess the resources as generators of competitive parity before the competition because classification as brave. Just received an assertive differentiated classification in the case of managers. And teachers also assessed some features not as valuable, a small minority considered them as valuable and rare resources and a slightly larger than this last installment assigns resources to the classification of valuable, rare and costly to imitate, according to the theory of model VRIO by Barney and Hesterly (2011)